1977
DOI: 10.1007/bf02671032
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vegetable oils for flavor quality by direct gas chromatography

Abstract: AND SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 11 publications
(4 reference statements)
1
21
0
Order By: Relevance
“…The differences found in oxidation rates between these studies could be due to differences in water activity of the powder, but also to differences in initial oxidative status of the product. Relationships between sensory changes and production of volatile oxidation products have been reported by numerous researchers (19,21,22) and a good correlation between hexanal production and sensory changes has been obtained (21,(23)(24)(25)(26)(27). In two previous studies, we investigated the effect of oxygen levels down to 0.3 mL/L oxygen in the headspace on the rate of lipid oxidation in cream powder (14,15).…”
Section: Introductionmentioning
confidence: 86%
“…The differences found in oxidation rates between these studies could be due to differences in water activity of the powder, but also to differences in initial oxidative status of the product. Relationships between sensory changes and production of volatile oxidation products have been reported by numerous researchers (19,21,22) and a good correlation between hexanal production and sensory changes has been obtained (21,(23)(24)(25)(26)(27). In two previous studies, we investigated the effect of oxygen levels down to 0.3 mL/L oxygen in the headspace on the rate of lipid oxidation in cream powder (14,15).…”
Section: Introductionmentioning
confidence: 86%
“…Frozen samples (.5 g) in headspace vials (5 mL) were thawed at room temperature for 30 min followed by heating at 80 C for 30 min inside the sampler magazine. Headspace volatiles from each vial were semiautomatically injected into the GC system (Sigma 2000 Gas Chromatograph with HS-6 Headspace Sampler, Perkin Elmer Corp., Norwalk, CT) and separated with a packed column of 8% polymetaphenoxylene on Tenex GC (Dupuy et al, 1977) treatment (TRT, control vs. inoculated), raw storage time (DAY), and replication (REP). The interaction of TRT x DAY was also tested.…”
Section: Methodsmentioning
confidence: 99%
“…The chromatograms (Figure 7-3) indicated that markedly higher quantities of off-flavor components were formed during storage of canola oil in clear glass bottles than for comparable oils in amber glass bottles. Moreover, comparisons of these chromatograms (Figure 7-3) with those determined by others for soybean, sunflower, and com oils (Dupuy et al 1977;Jackson and Giacherio 1977;Williams and Applewhite 1977;Min 1981;Min and Wen 1983) showed differences. Some unidentified volatiles present in canola oil in large amounts such as peak No.…”
Section: Volatile Decomposition Products and Their Effects On Oil Quamentioning
confidence: 60%
“…Snyder et al (1985) noted that volatile compounds in vegetable oils are related to the major fatty acids of the oil. Butane, pentane, and 2,4-decadienals have been determined to be the most important flavor components in vegetable oils (Dupuy et al 1977;Williams and Applewhite 1977;Min 1981;Min and Wen 1983;Waltking and Goetz 1983;Tokarska et al 1986). Although researchers (Scholz and Ptak 1966;Jarvi et al 1971;Blumenthal et al 1976;Snyder et al 1985;Tokarska et al 1986) have employed GC to assess the oxidative state of oils, reports of the application of this technique for evaluations of canola oil stability appear to be more limited.…”
Section: Assessment Of Oil Qualitymentioning
confidence: 99%